Assessing the Impact of Ambient Ozone on Growth and Yield of Crop at Rampur, Chitwan - Kharel, K.; Amgain, L. P. (Journal of Agriculture and Environment, 2010)
An experiment was conducted at Institute of Agriculture and Animal Science, Rampur, Chitwan, Nepal during March-July 2008 to explore the impact of ambient ozone on crop growth and yield. Mungbean cultivar "Pratikshya" was used as a test crop for the study. Mungbean plants were planted in 40 pots and 50% of the plants (i.e. plants in 20 pots) were treated with ethylenediurea (EDU) from 13 DAS to crop maturity at 10 days intervals. The ambient ozone level of the site was measured with passive samplers. The ozone level ranged from 29.3 to 39.1 ppb at the experimentation site during the cropping period. It was found that the ambient ozone at the site caused significant effects on plant growth and yield. The observed ambient ozone was found to reduce the growth parameters like plant height, per plant number of leaves, and number of branches by 10%, 27.74%, and 10.88%, respectively at 70 DAS while it reduced per plant number of seeds (13.17%), seed dry weights (19.67%), test weight (g/1000 seeds), (10.28%), total above-ground biomass (16.60%), harvest index (6.25%), and shelling percentage (5.07%) of controlled over EDU treated plants (ozone protected). The study clearly indicated that ambient ozone contributes to lower plant growth and crop yield. Key words: Ambient ozone; Ethylenediurea (EDU); Passive sampler The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 40-45 Uploaded Date: 15 Septembre, 2010